Neurocritical care board review - Zakaria, Asma (Demos Medical Publishing, 2013)
Neurocritical Care Board Review: Questions and Answers provides clinicians with a thorough review of the complex subspecialty of Neurocritical Care, using a question-and-answer (Q & A) format. The Q & A format is easily readable, high yield, and serves as good practice for test takers or anyone looking to improve or reinforce essential knowledge. The book covers the key topics pertinent to (and found on) neurocritical care boards, and is organized according to the exam core curriculum outline. A total of 649 questions address both neuroscience critical care (general neurology, neurotrauma, neurov.